Autonomous ships : evolution or revolution? - Keh, Cassandra Xiao Ting (Nanyang Technological University, 2020)
In recent years, autonomous vessels used for commercial trade have gained considerable attention. They advertised benefits such as enhanced safety, energy efficiency, increased flexibility and lower crew costs. While the rapid improvement in maritime shipping technological efficiency is accomplished by exploiting fast-improving technical domains (e.g. computer processors, sophisticated cameras, and sensors), this does not mean that autonomous vessels would become the ship owner's preferable option. In the end, the adoption of autonomous vessels essentially relies on its effect on the company's profitability. Therefore, this paper aims to analyse the cost benefits, prevalence and attractiveness of an autonomous ship market. Firstly, this study analyses the cost of operating an autonomous container vessel using a structured methodology and compares them to a traditional manned vessel in a cost-benefit analysis. It offers information on the economic advantages of autonomous vessels. Mainly, the findings reflect an economic potential. The operating cost of an unmanned vessel is about 1.4 times lower than that of a conventional manned vessel and yields a time charter equivalent that is about 2.1 times higher than a manned vessel. Secondly, the report analyses the prevalence of the autonomous ship concept and actions taken to adopt unmanned vessels in the market through a stakeholder profiling analysis. The results revealed that the current shipping market is dominated by traditionalist and observers, thereby forming a resistive force against the adoption of autonomous ships due to their wait-and-see approach. Lastly, as autonomous shipping is hindered by a set of challenges due to the lack of legal framework and cyber security issues within the international trade, a Porter Five Forces analysis is also carried out to assess the attractiveness of an autonomous ship market from a competitive standpoint. The results indicated that the competitive landscape for autonomous shipping is undesirable for shipowners and managers alike to enter the market due to the vigorous competition and strong power of buyers and suppliers. Currently, autonomous vessel applications are just abstract thought experiments and are still in the early phases of development. As more unmanned vessel designs and ideas evolve over the coming years on a more comprehensive basis, these will be the basis for further research into the commercial value of unmanned vessels. As such, this paper has also provided suggestions for future research areas.